2018
DOI: 10.1038/s41598-018-30727-9
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Memdiodes Exhibiting Rectification and Hysteresis for Neuromorphic Computing

Abstract: Metal-Nb2O5−x-metal memdiodes exhibiting rectification, hysteresis, and capacitance are demonstrated for applications in neuromorphic circuitry. These devices do not require any post-fabrication treatments such as filament creation by electroforming that would impede circuit scalability. Instead these devices operate due to Poole-Frenkel defect controlled transport where the high defect density is inherent to the Nb2O5−x deposition rather than post-fabrication treatments. Temperature dependent measurements rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…However, it has been shown that if controllable, hysteresis can be harnessed in neuromorphic devices as a short- or long-term memory effect. 8,10,38 In this regard, we examine the hysteresis in the transfer curves of our PEDOT:PSS-based solid OECTs and show how its magnitude can be controlled.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that if controllable, hysteresis can be harnessed in neuromorphic devices as a short- or long-term memory effect. 8,10,38 In this regard, we examine the hysteresis in the transfer curves of our PEDOT:PSS-based solid OECTs and show how its magnitude can be controlled.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are explained in Figure b, which shows the XPS spectra of the Nb 3d core region during the annealing processes. There are two niobium oxidation regions that are distinguished by references (vertical lines) of previously investigated amorphous Nb 2 O 5 (Nb 5+ ) and NbO 2 (Nb 4+ ) thin films. The Nb 5+ oxidation state is assigned to the immediate surface, while the Nb 4+ oxidation state is attributed to the subsurface and bulk, agreeing with vanadium oxidation states in VO 2 thin films .…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) was used to determine the ratio of Nb and O atoms in the films. 27 The Nb:O ratios of films with different growth powers are shown in Table 1.…”
Section: Sample Structurementioning
confidence: 99%